STATUS RESISTENSI NYAMUK AedesaegyptiTERHADAP MALATHION DI WILAYAH KERJA KKP KELAS III LHOKSEUMAWE(BerdasarkanUji Impregnated Paper danBiokimia) - Syahrizal Syahrizal; Retno Hestiningsih; Martini Martini (Jurnal Kesehatan Masyarakat (Undip), 2016)
Focus fogging in KKP Class III Lhokseumawe conducted every 3 months according to Standard Operating Procedures. Fogging activities carried out although there are cases. The use of insecticides for long periods can lead to insect resistance to organophosphate isektisida. This study aims to determine the resistance status of Ae. aegypti to malathion.Research conducted at the KKP Work Area Class III Lhokseumawe, larvae samples taken from three different areas, among others Kruenggeukueh Ports, Ports and Airports MalikussalehHaguPertamina. F1 mosquito rearing results in resistance tests using the susceptibility test kits and impregnated Paper malathion 0.8%, which is where the mosquito mortality was observed after 24 hours. Results showed death Ae.aegypti mosquitoes in the region 3 is 2%, 3% and 0 means that have been resistant to malathion. Malathion can not be used again by the Port Health Office Class III Lhokseumawe proved to be the death of Ae. aegypti is less than 80% so it needs to be replaced with another class of insecticides such as group Pirethroid (deltamethrin, Lambdasihalotrin, and cypermetrin)